A calculus problem by Zulqarnain Ansari

Calculus Level 2


The answer is 0.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

2 solutions

Rajen Kapur
Aug 14, 2015

Let t = t a n θ 2 t = tan\frac{\theta}{2} . Then x = c o s θ , y = s i n θ x = cos\theta, y = sin\theta . Then d y d x = c o t θ \frac{dy}{dx} = -cot\theta and therefore the given expression is equal to 0.

Curtis Clement
Aug 14, 2015

Using the identity ( 2 x y ) 2 + ( x 2 y 2 ) 2 = ( x 2 + y 2 ) 2 \ (2xy)^2 +(x^2 -y^2)^2 = (x^2 +y^2)^2 leads to ( 1 t ) 2 + ( 2 t ) 2 = ( 1 + t 2 ) 2 \ (1-t)^2 +(2t)^2 = (1+t^2)^2 x 2 + y 2 = 1 \therefore\ x^2 +y^2 = 1 Now differentiating implicitly with x gives: 2 x + 2 y . d y d x = 0 \ 2x +2y.\frac{dy}{dx} = 0 y . d y d x + x = 0 \therefore\ y.\frac{dy}{dx} +x = \boxed{0}

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...